Escravidão contemporânea no Maranhão: um estudo sobre mulheres em condições análogas às de escrava e as políticas estaduais de resgate - SOUSA, Karine Sandes de (2023)
The object of this research is the contemporary slavery in the state of Maranhão, most notably regarding the rescue of women subject to this category of exploitation, and the effectiveness of the State Program of Confrontation against the Unfree Labor in Conditions Analogous to Slavery (Programa Estadual de Enfrentamento ao Trabalho em Condições Análogas à de Escravo) as a way of access to the Fundamental Rights of liberty, dignity of human person, and social reinsertion. The research is structured in the general goal of identifying what is the real contribution of the State Department of Human Rights and Public Participation (Secretaria de Estado de Direitos Humanos e Participação Popular, “SEDIHPOP”), within the scope of the State Program of Confrontation, and the access to the above-mentioned Fundamental Rights regarding the unfree working women rescued in the state of Maranhão, based on the main theoretical framework of: Dworkin (2002, 2005, 2014), Sarlet (2011, 2016), Delgado e Delgado (2017), Santana (2021), Chai (2004, 2022), Schwarz (2008), Chaves (2016), Miraglia (2016), Sen (2010, 2011) and Sousa (2011). Concerning the methodological pathway, the inductive reasoning and the scientific method along with the legal-descriptive and the legal-propositional methods have been adopted. The research techniques applied were the bibliographic annotations together with the utilization of questionnaires for data collection, producing a documentary exploratory research with a qualitative and quantitative nature. Deriving out of the results that have been obtained, the initially proposed axiom is confirmed, stating that the performance of the SEDIHPOP grants the Fundamental Rights to the women even though its invisibility factor is a negative element in the composition of the data collected from the rescues. As general conclusion, it is possible to identify that the fulfillment of the actions from the Confrontation Program is constant, however there is an obstacle: the challenge in proceeding with the follow-ups and verification of the effectiveness of the actions to the detriment of the rescues made, in a way that the re-enticement is hindered, and the social reinsertion is effective enough to promote the adequate liberty as personal and community development of the rescued women. Moreover, it is possible to conclude that the specialized performance is somewhat timid, considering that the concern with the gender element has been proposed by the Program of Confrontation itself.